Cisplatin-induced early and delayed emesis in the pigeon - Tanihata, Sachiko (2000)
1. Intravenously injected cisplatin at a dose of 4 mg kg(−1) induced early and delayed emesis in all pigeons without occurrence of lethality during a 72 h observation period. The early emetic response occurred with a latency of 81.3±8.0 min (n=15) and reached a peak at 2–3 h, and decreased gradually within 8 h after injection. Then the delayed emetic response, whose peak was found between 10 to 23 h, lasted up to 48 h. The emetic response markedly declined after 48 h. 2. Reserpine markedly reduced monoamine levels in both brain and intestine and completely abolished the early and delayed emesis. Dexamethasone markedly reduced not only the early but also the delayed emetic responses. p-Chlorophenylalanine decreased the level of serotonin in brain and intestine without affecting noradrenaline and dopamine and partly reduced the early emetic response, but did not affect delayed emesis. 3. Bilateral vagotomy prolonged the latency time to the onset of early emesis, and reduced the emetic responses in both the early and delayed phases. 4. The above results suggest that the cisplatin-induced early emesis in the pigeon is partially mediated via the vagal nerve and reserpine-sensitive monoaminergic systems including the serotonergic system; the delayed emesis is associated with monoaminergic but not the serotonergic systems.